Pesticides - Beena Kumari; Kathpal, T.S (New Delhi New India)
This book provide the traditional as well as modern analytical techniques used for sample preparation of different matrices for extraction.
Adsorption Aerosol AFID
Keywords: Adsorption, Aerosol ,AFID